Identification of exhaust hanger location based on finite element model updating technique - Mohd Sahril, Mohd Fouzi (2020)
The development of exhaust structure to date has risen concerned among researchers and engineers due to the identification of suitable hanger location to suspend the structure on the vehicle’s chassis. This is because dynamic loads produced from uneven road condition and engine operational vibration that are transferred via hangers and propagated along the structure will affect the performance and lifespan of the exhaust structure. Hence, the present study proposed an approach to identify the best exhaust hanger location in order to improve the dynamic behaviour of the structure based on finite element (FE) model updating technique using normal mode analysis. Initially, the exhaust structure was modelled in computer aided design (CAD) software and imported into finite element analysis (FEA) software for pre-processing procedure. During the pre-processing phase, the FE model was treated with joint modelling strategy to represent the real welded exhaust structure since the joint itself gives a significant influence in the dynamic behaviour of a structure. Through joint modelling strategy, several element connectors such as rigid body element type 2 (RBE2), bar element connector (CBAR), beam element connector (CBEAM), and spring element connector (CELAS) available in the FEA software were used to model the welded joints. In order to verify the most reliable FE model with element connectors, the measured dynamic data from experimental modal analysis (EMA) were used and compared with the predicted result computed in FEA through correlation analysis. The measured dynamic data in this study were obtained from EMA using impact excitation with roving accelerometer technique. It was found that the FE model with CBAR element connector is feasible to replicate the real welded exhaust structure since it has the lowest discrepancy in correlation analysis. The discrepancy between the predicted results and its measured counterpart is appeared due to simplification made in modelled the complex geometry of exhaust structure and assumptions of material properties used during modelling process. Hence, FE model updating technique was adopted to reduce the discrepancy by adjusting the parameters iteratively. Prior to the updating process, sensitivity analysis was performed to select only sensitive parameters to be updated. The updating procedure managed to reduce the discrepancy from 4.10 % of error to 3.74 % of error. Then, the updated FE model was used for further analysis in identifying the best exhaust hanger location. In identifying the best hanger location, several case studies were designed with 35 numbers of hanger configurations. These hanger configurations for the FE model were computed using modal frequency response to evaluate its dynamic performance. Significantly, the maximum displacement of the original hanger location which was above 10 mm was successfully reduced less than 1 mm obtained from the 9th configuration. As a conclusion, a reliable FE model of welded exhaust structure has been successfully developed using joint modelling strategy and model updating technique, which later was effectively used in identifying the best hanger location numerically in minimizing the vibration effect with the reduction of displacement of the structure. This proposed method is valuable to be extended for other types of exhaust structures in identifying the best hanger location without involving any modification on the physical structure, which requires extra costs, efforts and time.